2015
DOI: 10.1016/j.jare.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artemether on cytokine profile and egg induced pathology in murine schistosomiasis mansoni

Abstract: Artemether (ART), the methylated derivative of artemisinin, is an efficacious antimalarial drug that also displays antischistosomal properties. This study was designed to evaluate the immunomodulatory action of a single intramuscular dose (50 mg/kg body weight) of ART in comparison with PZQ treatment (42 days PI). ART administration was 7, 14, 21 and 45 days PI. ART effect was studied parasitologically, histopathologically and immunologically. It was found that maximum effect was reached when ART treatment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Our results also showed an increased egg burden of the liver in the TLR2-activated MSC group or decreased egg burden in the TLR4-activated MSC group, which appeared atrophy of the thymus or improved structure of the thymus, respectively. Many results also showed the correlation of Th1-type polarization with the reduction of liver eggs [25][26][27][28]. Our results also showed that the lower egg burden appeared in the TLR4-activated MSC group which had the highest level of IFN-γ and alleviated damage to the liver.…”
Section: Discussionsupporting
confidence: 67%
“…Our results also showed an increased egg burden of the liver in the TLR2-activated MSC group or decreased egg burden in the TLR4-activated MSC group, which appeared atrophy of the thymus or improved structure of the thymus, respectively. Many results also showed the correlation of Th1-type polarization with the reduction of liver eggs [25][26][27][28]. Our results also showed that the lower egg burden appeared in the TLR4-activated MSC group which had the highest level of IFN-γ and alleviated damage to the liver.…”
Section: Discussionsupporting
confidence: 67%
“…Artemether showed anti-parasitic properties toward many protozoan parasites such as Leishmania, Toxoplasma gondii and Trypansoma spp. (Mishina et al, 2007), and also a promising drug in control of schistosomiasis mansoni due to its reductive impact on worm burden and its role in improvement of hepatic granulomatous lesions (Madbouly et al, 2015). Production of artemisinin in genetically modified microorganisms is an attractive way to enable sufficient supply of the effective antimalarial agent (Zeng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was first described as anti-schistosomal agent in 1980s, against juvenile worms (5-21day-old) S. japonicum ( Liu et al, 2012 ). Artemether efficiency as a schistosomicidal and molluscicidal agent has been previously shown ( Al-Kazzaz et al, 2014 ; Madbouly et al, 2015 ).…”
Section: Introductionmentioning
confidence: 93%